Alpha-hederin reprograms multi-miRNAs activity and overcome small extracellular vesicles-mediated paclitaxel resistance in NSCLC - Chang, Yuzhen; Gao, Xinyu; Jiang, Yuchen; Wang, Jingyi; Liu, Liu; Yan, Jun; Huang, Gang; Yang, Hao (Frontiers in Pharmacology, 2024)
Background: Small extracellular vesicles (sEVs) mediate intercellular communication in the tumor microenvironment (TME) and contribute to the malignant transformation of tumors, including unrestricted growth, metastasis, or therapeutic resistance. However, there is a lack of agents targeting sEVs to overcome or reverse tumor chemotherapy resistance through sEVs-mediated TME reprogramming. Methods: The paclitaxel (PTX)-resistant A549T cell line was used to explore the inhibitory effect of alpha-hederin on impeding the transmission of chemoresistance in non-small cell lung cancer (NSCLC) through the small extracellular vesicles (sEVs) pathway. This investigation utilized the CCK-8 assay and flow cytometry. Transcriptomics, Western blot, oil red O staining, and targeted metabolomics were utilized to evaluate the impact of alpha-hederin on the expression of signaling pathways associated with chemoresistance transmission in NSCLC cells before and after treatment. In vivo molecular imaging and immunohistochemistry were conducted to assess how alpha-hederin influences the transmission of chemoresistance through the sEVs pathway. RT-PCR was employed to examine the expression of miRNA and lncRNA in response to alpha-hederin treatment. Results: The resistance to PTX chemotherapy in A549T cells was overcome by alpha-hederin through its dependence on sEV secretion. However, the effectiveness of alpha-hederin was compromised when vesicle secretion was blocked by the GW4869 inhibitor. Transcriptomic analysis for 463 upregulated genes in recipient cells exposed to A549T-derived sEVs revealed that these sEVs enhanced TGFβ signaling and unsaturated fatty acid synthesis pathways. Alpha-hederin inhibited 15 types of unsaturated fatty acid synthesis by reducing the signaling activity of the sEVs-mediated TGFβ/SMAD2 pathway. Further, we observed that alpha-hederin promoted the production of three microRNAs (miRNAs, including miR-21-5p, miR-23a-3p, and miR-125b-5p) and the sorting to sEVs in A549T cells. These miRNAs targeted the TGFβ/SMADs signaling activity in sEVs-recipient cells and sensitized them to the PTX therapy. Conclusion: Our finding demonstrated that alpha-hederin could sensitize PTX-resistant NSCLC cells by sEV-mediated multiple miRNAs accumulation, and inhibiting TGFβ/SMAD2 pathways in recipient cells.